Status of Serum Iron and Copper in Women Taking Oral Contraceptive (Bangladesh Journal of Medical Biochemistry, 2018)
The oral contraceptive pill fulfills the great human need for birth control with unrivalled effectiveness. The pill can effectively prevent pregnancy and alleviate many menstrual disorders when used correctly. Many biochemical profiles of women taking oral contraceptives are disturbed due to metabolic alterations induced by its hormone content. The study was carried out in the Department of Biochemistry, Mymensingh Medical College, Mymensingh, during the period of July 2016 to June 2017 to evaluate the status of serum iron and copper in women taking oral contraceptive pills. For this study 120 agematched women were selected and grouped as 60 oral contraceptive user women and 60 non-oral contraceptive user women. Data were analyzed with the help of SPSS version 21. Mean(±SD) level of serum iron and copper were 155.20±21.94 mg/dl and 157.6±14.75 mg/dl in oral contraceptive user women, while in normal healthy women the levels were 103±19.11 mg/dl and 126.28±17.18 mg/dl respectively. Serum iron and copper levels were significantly increased in oral contraceptive user group when compared with that of normal healthy group (p